(untitled) (World Bulletin of Management and Law, 2022)
Crude Oil (Petrol) plays an important role in the economy of Iraq, since the establishment of the modern Iraqi state in 1921 AD, the Crude Oil sector has had a major role in financing development projects in the country. However, this importance has increased since 1951, where the Crude Oil revenues began increase to become the main financier of the public budget, thus economic development in Iraq has become dependent on public revenues, especially Oil revenues. After 2003, as a result of the lifting of the economic blockade and the rise of Crude Oil prices on the other hand, the Crude Oil revenues increased and the budget was greatly affected by the increasing of Crude Oil revenues . The study aimed to clarify the analysis of the evolution of the general budget structure (public expenditures and revenues) in Iraq, through the fluctuations in Crude Oil prices, and to determine the percentage of the contribution of Crude Oil price fluctuations to explaining the changes that occur at the level of the public budget balance in Iraq of the period (2010- 2017). The study concluded that Iraq occupies a great and distinguished position among the world’s Crude Oil countries, whether in terms of its proven Crude Oil potential or reserves, and it ranks third in the world behind Saudi Arabia and Venezuela, where it has proven reserves of (143) billion barrels and a potential reserve of ( 350) billion barrels that qualifies it to be the first Crude Oil producing and exporting country in the world in the coming years. Iraq’s Crude Oil revenues increased after 2003 to 2012 , as a result of the rise in global Crude Oil prices, then revenues began to decline, specifically from 2014 to 2017 and could not cope continuing expenses in most years of study due to the security and political situations that the country has experienced .